Penerapan Mediasi dalam Penyelesaian Sengketa Perdata di Pengadilan Negeri Yogyakarta Tahun 2012-2013: Studi Peraturan Mahkamah Agung Nomor 1 Tahun 2008 - Erina Qurrota Ainy (UIN Sunan Kalijaga Yogyakarta, 2014)
One of the problems faced by the judiciary in Indonesia that there is a largenumbers of buildup cases. On the other hand, the community, especially those who’sseeking for justice want these problems can be solved immediately. For this reason theSupreme Court issued PERMA No. 1 Tahun 2008 about Mediation Procedures inCourt. The integration of mediation into the court proceedings expected to be one of theeffective instruments to address the buildup of the case. The Yogyakarta State Court asone of the first instance court in Indonesia should always seek mediation as a means ofsettlement of civil disputes. This is consistent with PERMA No. 1 Tahun 2008about Mediation Procedures in Court which require mediation before proceedings. Fromthe available data the percentage of successful mediation in Yogyakarta state Court in2012 and 2013 which is about 4.26% and 1.91% respectively of 164 and 157 civilcases were entered. This research is a field research, which examines the application ofmediation in resolving civil disputes in Yogyakarta State Court Year 2012-2013according to PERMA No. 1 Tahun 2008 and the constraints in its implementation.To answer these problems the authors use juridical empirical approach in which theLegislation relating to these issues serves as the reference material for research. Then allthe data is analyzed by descriptive-analytic.